Epstein-Barr Virus–Positive CD20- and CD45-Negative Diffuse Large B-Cell Lymphoma: A Diagnostic Challenge. (February 2019) - Starr, Amy; Kwon, Dong Hyang; Kallakury, Bhaskar
Diffuse large B-cell lymphoma (DLBCL) is characterized by medium- to large-sized neoplastic cells that express a wide range of B-cell markers including CD19, CD20, CD22, and CD79a. Also, as this is a hematopoietic malignancy, there is expression of the leukocyte common antigen CD45. Lack of CD20 expression occurs in a specific rare heterogeneous subgroup of DLBCL including primary effusion lymphoma, plasmablastic lymphoma, ALK-positive large B-cell lymphoma, and large B-cell lymphoma arising in HHV8+ multicentric Castleman disease. In this article, we report a rare case of CD20- and CD45-negative Epstein-Barr virus–positive DLBCL in which the entities listed above were ruled out, thereby posing a significant diagnostic challenge. Arriving at the correct diagnosis of Epstein-Barr virus–positive DLBCL was supported by immunoreactivity for the B-cell transcription factor Oct-2 and the pan-B cell marker CD79a.